Feste Benzinpreise für einen Tag: Mehr Preiswettbewerb durch die 24h-Regel? - Andreas Reindl; Thomas Wein (Wirtschaftsdienst, 2012)
Die Erhöhung der Benzinpreise findet in der Öffentlichkeit viel Beachtung. Das Bundeskartellamt geht in Deutschland von einem marktbeherrschenden Oligopol der Mineralölgesellschaften aus. Wettbewerbsrechtliche Maßnahmen greifen jedoch nicht, weil der Markt sehr volatil ist und direkte Preisabsprachen nicht nachgewiesen werden können. In Westaustralien sollen überhöhte Benzinpreise mit einer 24h-Regel verhindert werden, die auch für Deutschland eine Möglichkeit darstellt. – – The German Cartel Office's recent study of retail gasoline markets provides strong evidence of an oligopoly in which the major suppliers coordinate pricing strategies and achieve supracompetitive prices. Competition law enforcement does not provide effective tools to improve market outcomes. We examine the potential benefits of a regulatory framework that would require gasoline suppliers to announce at a specified time their prices for the following day and prohibit price changes during a 24-hour period. Such a 24-hour rule could complicate coordination and lead to lower prices, although it cannot be ruled out that the oligopolists would adjust and develop new coordination strategies.
Keywords: D43; L13; L51; 330